Synthesis, characterization and fuel parameters analysis of linseed oil biodiesel using cadmium oxide nanoparticles. (1st May 2021) - Tariq, Muhammad; Qureshi, Ahmad Kaleem; Karim, Shaista; Sirajuddin, Muhammad; Abbas, Naseem; Imran, Muhammad; Shirazi, Jaffir Hussain
Abstract: Linseed oil biodiesel (LSOB) was synthesized from linseed oil by cadmium oxide nanoparticles applying transesterification reaction of oil with methanol. Cadmium oxide nanoparticles were synthesized through the hydrothermal method using cadmium acetate as precursor, sodium hydroxide for precipitation and urea as capping agent. The main analytical tools such as FT-IR, powder XRD and SE microscope were used to characterize newly prepared cadmium oxide nanoparticles. The appearance of new absorption band at 670 cm −1 has been assigned to Cd–O stretching vibration. XRD pattern indicate the purity and gave average particle size of 52 nm by Debye-Scherer formula. SEM images show granular shape of cadmium oxide nanoparticles with average particle size of 43 nm. The formation of linseed oil biodiesel was investigated using FT-IR and proton & carbon-13 NMR. GC-MS analysis of linseed oil biodiesel indicated six types of fatty acid methyl esters ranging from C16–C22 (mixture of both saturated and unsaturated). The fuel properties such as density, viscosity, cloud, pour and flash point were determined and compared with both ASTM standards for biodiesel and diesel. Highlights: LSOB synthesized from linseed oil using cadmium oxide nanoparticles. Cadmium oxide nanoparticles were synthesized through the hydrothermal method. CdO NPs characterized by FT-IR, powder XRD and SEM. Transesterification reaction of linseed oil with methanol was done to produce LSOB. LSOB characterized by IR, NMR & GC-MS & Fuel properties by ASTM methods.